2019
DOI: 10.1186/s40425-019-0587-z
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination with nanoparticles combined with micro-adjuvants protects against cancer

Abstract: Background Induction of strong T cell responses, in particular cytotoxic T cells, is a key for the generation of efficacious therapeutic cancer vaccines which yet, remains a major challenge for the vaccine developing world. Here we demonstrate that it is possible to harness the physiological properties of the lymphatic system to optimize the induction of a protective T cell response. Indeed, the lymphatic system sharply distinguishes between nanoscale and microscale particles. The former reaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…(b) Mix multi‐target VLP‐based vaccine consisting of germline and mutated CTL epitopes coupled to Qβ‐VLPs by Cu‐free click chemistry and loaded with B‐type CpGs (Mohsen, Vogel, et al, ). (c) A microcrystalline tyrosine crystal decorated with CuMV TT ‐p33 nanoparticles labeled with AF488 (Mohsen, Heath, et al, )…”
Section: Virus‐like Particles As Therapeutic Cancer Vaccines: Preclinmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Mix multi‐target VLP‐based vaccine consisting of germline and mutated CTL epitopes coupled to Qβ‐VLPs by Cu‐free click chemistry and loaded with B‐type CpGs (Mohsen, Vogel, et al, ). (c) A microcrystalline tyrosine crystal decorated with CuMV TT ‐p33 nanoparticles labeled with AF488 (Mohsen, Heath, et al, )…”
Section: Virus‐like Particles As Therapeutic Cancer Vaccines: Preclinmentioning
confidence: 99%
“…(b) Mix multi-target VLP-based vaccine consisting of germline and mutated CTL epitopes coupled to Qβ-VLPs by Cu-free click chemistry and loaded with B-type CpGs (Mohsen, Vogel, et al, 2019). (c) A microcrystalline tyrosine crystal decorated with CuMV TT -p33 nanoparticles labeled with AF488 (Mohsen, Heath, et al, 2019) inhalation of eCPMV triggered the activation and accumulation of neutrophils in the lungs accompanied with an increase in neutrophil-associated chemokines and cytokines. The study concluded that the anti-tumor effects induced by eCPMV required neutrophils.…”
Section: Vlp-based Vaccines Against Melanomamentioning
confidence: 99%
“…VLPs adjuvanted with MCT effectively retarded the development of the tumor. The effect was comparable when CpG DNA was used as the adjuvant, whereas alum was ineffective in slowing down tumor growth [69].…”
Section: Plant Viruses Including Both Native and Recombinant Virusesmentioning
confidence: 97%
“…The addition of the micron-sized MCT adjuvant of ~ 5 μM resulted in a local depot for the nanoparticles and a longer exposure to the immune system, eliciting an enhanced specific T cell response in the stringent B16F10p33 murine melanoma model. The study showed that the micron-sized MCT adjuvant was as potent as B type CpGs and superior to the alum adjuvant [72].…”
Section: Virus-like Particlesmentioning
confidence: 98%